2014
DOI: 10.5558/tfc2014-097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerial strip spraying on mixedwood stand structure and tree growth

Abstract: Herbicide application in strips offers a cost-effective way to accelerate spruce growth in young mixedwood stands, while also retaining the mixedwood character of the stand. In June of 2006 data were collected to evaluate the effects of aerial strip spraying on subsequent growth of treated stands. These blocks had been planted in 1991 and treated in 2000 with Triclopyr ester herbicide applied in strips. Treated and untreated strips averaged 5.8 m and 8.4 m in width, respectively, with 38% of the block area bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…However, the benefits of two herbicide treatments were evident, as diameter in this treatment was nearly double that of the untreated areas 11 years after planting. Other studies have reported consistent findings; for instance, Comeau [33] reported that spruce diameter increment following triclopyr herbicide treatment was 1.8 times that of control plots, while triclopyr treatment increased stem volume index by 1.7 times. Bell et al [28] reported similar increases in spruce volume ten years after aerial triclopyr treatment.…”
Section: Discussionsupporting
confidence: 52%
“…However, the benefits of two herbicide treatments were evident, as diameter in this treatment was nearly double that of the untreated areas 11 years after planting. Other studies have reported consistent findings; for instance, Comeau [33] reported that spruce diameter increment following triclopyr herbicide treatment was 1.8 times that of control plots, while triclopyr treatment increased stem volume index by 1.7 times. Bell et al [28] reported similar increases in spruce volume ten years after aerial triclopyr treatment.…”
Section: Discussionsupporting
confidence: 52%
“…If aspen is allowed to "catch-up" after brushing, the inevitable competition impacts to planted pine growth and survival will return. Knowledge of how aspen responds to various brushing treatments can be used to help set acceptable thresholds of aspen size and frequency within mixedwood prescriptions (Comeau 2014). …”
Section: Discussionmentioning
confidence: 99%
“…and white spruce (Picea glauca (Moench.) Voss), also with 20 % transgressive over-yielding (Kabzems et al 2007;Comeau 2014). Additional gain is expected by combining this approach with e.g.…”
Section: Two-storied Mixed Plantationsmentioning
confidence: 99%